Caspase-independent apoptosis in infected macrophages triggered by sulforaphane via Nrf2/p38 signaling pathways - Bonay, M (Cell Death Discov, 2015)
Mycobacterium abscessus (Mabs), a non-tuberculous mycobacterium, is an emerging and rapidly growing opportunistic pathogen that is frequently found in patients with cystic fibrosis and in immunosuppressed patients. Its high tolerance to antibiotics is of great concern for public health. In this study, our results showed that human THP-1-derived macrophages infected with M. abscessus presented an increase in ROS production and cell necrosis. In addition, M. abscessus infection triggered activation of the Nuclear factor E2-related factor 2 (Nrf2) signaling pathway, and the induction of HO-1 and NQO1 expression levels. Interestingly, pretreatment of macrophages with sulforaphane (SFN), an activator of the antioxidant key regulator Nrf2, followed by M. abscessus infection significantly decreased mycobacterial burden. We demonstrated that this reduction in mycobacterial growth was due to an activation in cell apoptosis in SFN-pretreated and M. abscessus-infected macrophages. Pretreatment with specific MAPK inhibitors, PD98059, SP600125, and SB203580 to ERK, JNK, and p38 respectively, failed to inhibit induction of Nrf2 expression, suggesting that Nrf2 signaling pathway was upstream of MAPK signaling. Activation of cell apoptosis was caspase 3/7 independent but p38 MAPK dependent. Moreover, p38 MAPK induction was abolished in macrophages transfected with Nrf2 siRNA. In addition, p38 inhibitor abolished Nrf2-dependent apoptosis in infected macrophages. Taken together, our results indicate that modulation of the Nrf2 signaling using Nrf2 activators may help potentiate the actual drug therapies used to treat mycobacterial infection.